Amino acid-functionalized metal organic framework with excellent proton conductivity for proton exchange membranes. (1st January 2021) - Wang, Shubo; Luo, Huiling; Li, Xuan; Shi, Lei; Cheng, Bowen; Zhuang, Xupin; Li, Zhenhuan
Abstract: Proton conduction is a ubiquitous fundamental phenomenon in biological systems. Biology has solved the problem of energy-related proton conduction, in which the exposed amino acids in the protein ordered channels play a key role in proton conduction. In this contribution, amino acids (glutamate, lysine, and threonine) were attached to metal organic framework (MOF) nanoparticles, which were incorporated into sulfonated polysulfone matrix forming bio-proton channels for the nanocomposite membranes. It is shown in the results that the amino acid-functionalized MOF can help to enhance the proton conductivity and the proton exchange membrane with glutamate-functionalized MOF demonstrate excellent proton conductivity of 0.212 S cm −1 at 80 °C and 100% relative humidity. Meanwhile, the methanol permeability coefficient of the nanocomposite membrane is reduced to 5.8 × 10 −7  cm 2  s −1 . The nanocomposite membranes demonstrate excellent proton conductivity, dimensional stabilities, water absorption, and resistance to methanol performance. Therefore, this material is promising for fuel cells. Highlights: Amino acids were introduced onto UiO-66-NH2 by a post-synthetic modification. UiO-66-NH2 -AA were mixed with SPSF to get high-performance nanocomposite PEMs. UiO-66-NH2 -Glu/SPSF showed the highest proton conductivity of 0.212 S cm −1 at 80 °C. Introduction of UiO-66-NH2 -AA resulted in a reduced fuel crossover.